Hybridization and transgressive exploration of colour pattern and wing morphology in Heliconius butterflies. (26th April 2020) - Mérot, Claire; Debat, Vincent; Le Poul, Yann; Merrill, Richard M.; Naisbit, Russell E.; Tholance, Adélie; Jiggins, Chris D.; Joron, Mathieu
Abstract: Hybridization can generate novel phenotypes distinct from those of parental lineages, a phenomenon known as transgressive trait variation. Transgressive phenotypes might negatively or positively affect hybrid fitness, and increase available variation. Closely related species of Heliconius butterflies regularly produce hybrids in nature, and hybridization is thought to play a role in the diversification of novel wing colour patterns despite strong stabilizing selection due to interspecific mimicry. Here, we studied wing phenotypes in first‐ and second‐generation hybrids produced by controlled crosses between either two co‐mimetic species of Heliconius or between two nonmimetic species. We quantified wing size, shape and colour pattern variation and asked whether hybrids displayed transgressive wing phenotypes. Discrete traits underlain by major‐effect loci, such as the presence or absence of colour patches, generate novel phenotypes. For quantitative traits, such as wing shape or subtle colour pattern characters, hybrids only exceed the parental range in specific dimensions of the morphological space. Overall, our study addresses some of the challenges in defining and measuring phenotypic transgression for multivariate traits and our data suggest that the extent to which transgressive trait variation in hybrids contributes to phenotypic diversity depends on the complexity and the genetic architecture of the traits. Abstract : Hybrids between Heliconius melpomene amaryllis and Heliconius timareta thelxinoe (Peru). Quantifying wing phenotypes in 1st and 2nd generation hybrid butterflies suggests that hybridization contributes to phenotypic diversification, both for traits controlled by large‐effect genes such as wing pattern and, to a lesser extent, for polygenic traits such as wing shape.